2012
DOI: 10.1371/journal.pone.0036041
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulated Nephrin in Diabetic Nephropathy of Type 2 Diabetes: A Cross Sectional Study

Abstract: BackgroundPodocyte specific proteins are dysregulated in diabetic nephropathy, though the extent of their expression loss is not identical and may be subject to different regulatory factors. Quantifying the degree of loss may help identify the most useful protein to use as an early biomarker of diabetic nephropathy.Methodology/Principal FindingsProtein expression of synaptopodin, podocin and nephrin were quantified in 15 Type 2 diabetic renal biopsies and 12 control patients. We found statistically significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
115
2
6

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 154 publications
(133 citation statements)
references
References 36 publications
10
115
2
6
Order By: Relevance
“…Biomarkers, such as urinary albumin, neutrophil gelatinaseassociated lipocalin, KIM-1, IL-18, L-FABP MCP-1, nephrin, podocalyxin, and podocin, are markers of tubular or glomerular damage. [52][53][54][55] Other biomarkers, such as C-reactive protein and TNF receptor 2, which are general biomarkers of inflammation or endothelial dysfunction, may reflect systemic phenomena relevant to CKD progression, 56 but their predictive value after AKI is unknown.…”
Section: Question 4 Can Progression To Ckd Be Predicted After Aki Anmentioning
confidence: 99%
“…Biomarkers, such as urinary albumin, neutrophil gelatinaseassociated lipocalin, KIM-1, IL-18, L-FABP MCP-1, nephrin, podocalyxin, and podocin, are markers of tubular or glomerular damage. [52][53][54][55] Other biomarkers, such as C-reactive protein and TNF receptor 2, which are general biomarkers of inflammation or endothelial dysfunction, may reflect systemic phenomena relevant to CKD progression, 56 but their predictive value after AKI is unknown.…”
Section: Question 4 Can Progression To Ckd Be Predicted After Aki Anmentioning
confidence: 99%
“…Podocytes are terminally differentiated and highly specialized glomerular visceral epithelial cells that form part of the glomerular filtration barrier, which prevents urinary protein loss [2] . Several recent studies suggested that podocyte damage may play a key role in the pathogenesis of DN [3][4][5] .…”
Section: Introductionmentioning
confidence: 99%
“…12 This may be due to the cleavage of the extracellular domain of nephrin molecule which becomes undetectable (as all available antibodies recognize only the extracellular domain of nephrin) and/or to the loss of podocytes. Immunostaining of diabetic kidneys for nephrin and podocin in fact showed a reduction in staining area, rather than of staining intensity ( Figure 2B).…”
mentioning
confidence: 99%